Report from the 2nd World Calisia Conference on Family Health, Kalisz, Poland, 24–25 October 2021 - Janik-Koncewicz, Kinga; Cicharska, Renata (Journal of Health Inequalities, 2021)
The 2nd World Conference on Family Health, which took place at Calisia University on 24–25 October 2021, was a continuation of the deliberations on the health condition of families, launched during its first edition in 2019. This year the main conference theme was “Health at the time of crises and wars’’. The meeting was organized among others by the Institute – European Observatory of Health Inequalities at Calisia University. It was held under the honorary patronage of the Polish Ministry of Education and Science, the Ministry of Family and Social Policy and the Ministry of Health. During the inauguration ceremony a letter to the participants of the conference from Prime Minister Mateusz Morawiecki was read out.